Penyuluhan Tentang Pengelolaan Sampah di Jorong Tapi Aia, Kenagarian Kinari, Kabupaten Solok - Asyari, Dian Paramitha; Handiny, Febry; Rahma, Gusni (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2024)
Household Waste Management can be done by selecting waste between Organic Waste and Anorganic Waste. Based on the results of data processing which is obtained from the results of interviews from 145 respondents, 4 problems are obtained, namely, 100% of waste management that throws garbage into the river / gutter. Based on the Solok Regency Regional Regulation, the Regional Government is obliged to provide district-scale waste management facilities in the form of TPS, TPS 3R, Intermediate Transfer Station (SPA), TPA, TPST. The Regional Government is obliged to fund the implementation of waste management, provide waste sorting facilities consisting of 3 (three) types of waste, namely organic waste, inorganic waste and household hazardous waste. Based on this, it is necessary to carry out counselling activities and install banners prohibiting throwing garbage into rivers and sewers in order to create a clean and healthy environment without waste in Nagari Kinari.